Investigation of Crystal and Electronic Structures Features of Hf1-xTmxNiSn Semiconductor Solid Solution - Romaka, L.P.; Rogl, P.-F.; Нoryn A.M.; Krayovskyy, V.Ya.; Stadnyk, Yu.V.; Romaka, V.V. (Physics and Chemistry of Solid State, 2016)
The features of structural, energy state and electrokinetic characteristics were investigated for Hf1‑xTmxNiSn solid solution in the range: T = 80 - 400 K, x = 0 - 0.40. It was confirmed partly disorder crystal structure of HfNiSn compound as a result of occupation in the 4a crystallographic site of Hf (5d26s2) atoms by Ni (3d84s2) ones up to 1 % that generates in the crystal structural defects of donor nature. It was shown that introduction of Tm atoms ordered crystal structure (“healing” of structural defects). It was established mechanisms of simultaneous generation of structural defects as acceptors by substitution of Hf (5d26s2) by Tm (4f135d06s2) atoms, and the donor nature defects as a result of the appearance of vacancies in the Sn (4b) atoms sites, which determines the mechanisms of conductivity for Hf1-xTmxNiSn.